Dealing with the social media content and its relationship with personality Five-Factors’ of Sudanese psychologists - Suliman, Mohamed MohamedAlhadi; Elsir, Ahmed Suliman (Journal of Educational and Psychological Sciences, 2021)
The study aims to investigate the relationship between the styles of dealing with social media content and personality Five-Factor the Sudanese psychologist. The researchers used a style of dealing with social media, and the Five-Factor Inventory Costa & McCrae. The researchers applied the tools to a sample of 300 (males and females) Sudanese psychologist. The collected data analyzed statistically by SPSS. The results showed positive styles of Sudanese psychologist dealing with social media content and showed high levels of positive of the Sudanese psychologist, and showed a significant relationship between styles of dealing with social media and (Extraversion, Conscientiousness) of the Sudanese psychologist, and no significant relationship between styles of dealing with social media and (Neuroticism, Extraversion, Openness to Experience, Agreeableness, sex, age, social media). Finally, the researchers gave some recommendations depending on the research results.